2, 4-Dinitrophenol overdose - Everything old is new again. (April 2021) - Griffiths, A.; Milne, N.; Ong, B.; Watkins, T.
Abstract: A complete case example of a fatal 2, 4-dinitrophenol (DNP) overdose involving a 23-year-old male is described. Included are details of not only the patient's presentation symptoms and treatment, but also the subsequent findings of the coronial investigation process including the autopsy, post-mortem computed tomography (PMCT) scanning and toxicological analysis and results. The patient presented with elevated temperature, heart rate and blood pressure. Multiple treatments were conducted to counteract these symptoms, however the patient died approximately 1.5 hours after hospital admission and some 4.5 hours after the DNP was initially consumed. Autopsy revealed the presence of cardiovascular disease that was contributory to death and post-mortem computed tomography showed evidence of decompositional intravascular gas in the neck, head, face, lower abdomen, heart and hepatic systems. Toxicological analysis was completed by protein precipitation with methanol and subsequent instrumental analysis by LC/MS/MS in negative ion mode. The antemortem blood specimen showed the presence of tadalafil, two anabolic steroids and a DNP concentration of 110 mg/kg which is consistent with other reported DNP fatalities. Despite the small amount of time between the antemortem specimen collection and death, the DNP concentration identified in the femoral blood post-mortem specimen was comparably low (5.5 mg/kg). DNP concentrations also reduced during an extended period of specimen storage prior to analysis indicating some instability in biological specimens even when refrigerated or frozen. DNP was found to be distributed primarily in the aqueous tissues (blood, vitreous, bile) rather than solid matrices (liver, kidney, muscle). Highlights: A complete case example of a fatal 2, 4-Dinitrophenol (DNP) overdose is presented. Post-mortem computed tomography showed evidence of accelerated decompositional intravascular gas in multiple regions. Toxicological analysis showed an elevated ante-mortem blood DNP concentration of 110 mg/L. A large reduction in DNP concentration was identified in post-mortem specimens. DNP showed a higher distribution in liquid (blood, vitreous, bile) rather than solid matrices (liver, kidney, muscle).